1999
DOI: 10.1002/etc.5620180826
|View full text |Cite
|
Sign up to set email alerts
|

Chronic toxicity of 2,4,6‐trinitrotoluene to a marine polychaete and an estuarine amphipod

Abstract: The chronic toxicity of sediment‐associated 2,4,6‐trinitrotoluene (TNT) to the marine polychaete Neanthes arenaceodentata and the estuarine amphipod Leptocheirus plumulosus was evaluated. Test organisms were exposed to sediments spiked with radiolabeled TNT for 28 d, after which time the endpoints of mortality, growth, and reproduction (L. plumulosus only) were assayed and compared against the TNT tissue concentrations as well as the TNT sediment concentrations. Survival was significantly reduced at a tissue c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 48 publications
2
35
1
Order By: Relevance
“…A possible explanation is the phenomenon called hormesis, which can be identified as a growth enhancement induced by exposure to low doses of contaminant (Stebbing, 1997). This type of biological response has been already detected in G. locusta exposed to sediments spiked with copper (Correia et al, 2001) and has been increasingly reported in ecotoxicological studies, as for example sediment toxicity assessments with amphipods (Green et al, 1999) and other invertebrates (Martinez-Madrid, Rodriguez, Perez-Iglesias, & Navarro, 1999).…”
Section: Chronic Sediment Toxicity: Individual and Population Responsesmentioning
confidence: 91%
See 1 more Smart Citation
“…A possible explanation is the phenomenon called hormesis, which can be identified as a growth enhancement induced by exposure to low doses of contaminant (Stebbing, 1997). This type of biological response has been already detected in G. locusta exposed to sediments spiked with copper (Correia et al, 2001) and has been increasingly reported in ecotoxicological studies, as for example sediment toxicity assessments with amphipods (Green et al, 1999) and other invertebrates (Martinez-Madrid, Rodriguez, Perez-Iglesias, & Navarro, 1999).…”
Section: Chronic Sediment Toxicity: Individual and Population Responsesmentioning
confidence: 91%
“…Toxicity was expressed by the lower survival, particularly males, and a biased sex ratio, more evident in sediment D. These severe toxic effects were not apparent in growth of surviving animals. However, caution must be taken interpreting growth data from chronic tests when there were significant reductions in survival (Green, Moore, & Farrar, 1999;Ingersoll et al, 1998;Sibley, Benott, & Ankley, 1997). One main concern is that growth may have been affected by reduction of organism density on the course of the test.…”
Section: Chronic Sediment Toxicity: Individual and Population Responsesmentioning
confidence: 99%
“…Despite its fast elimination, mutagenic properties and noxious effects of TNT, such as reduced survival, growth and reproduction, have been documented in several aquatic organisms (Smock et al 1976;Johnson et al 2000;Green et al 1999;Talmage et al 1999). However, few studies have considered the physiological mechanisms behind these effects in fish species.…”
mentioning
confidence: 99%
“…However, others (Anderson et al, 1998;Bridges et al, 1997;Green et al, 1999) have reported reductions in N. arenaceodentata endpoints, more often expressed for growth than survival, in exposures to contaminated sediments. The 20-d method is documented in a routine testing program (DMMP).…”
Section: Discussionmentioning
confidence: 99%